THE DEVELOPMENT OF PICO HYDRO POWER PLANT BY UTILIZING IRRIGATION FLOW IN KASAMBANG VILLAGE OF MAMUJU REGENCY - Haripuddin Haripuddin; Andi Zauqi; Muhammad Yusuf Mappeasse; Massikki Massikki (Jurnal Media Elektrik, 2023)
Piko Hydro Power Plant (PLTPH) is one of the power plants that uses water as an energy source. Piko hydro is included in the category of hydropower with small power because there is no need to use too large a water discharge to produce power. The tool developed in this study is a Piko Hydro Power Plant by Utilizing Irrigation Flow. The purpose of the research is to determine the results of the development of Piko Hydro Power Plant equipment, the electrical energy produced, and the response of the community. The research method used is quantitative descriptive with the type of Research and Development (R & D) research and prototype development model consisting of 4 steps, namely needs analysis, building prototypes, installing, and evaluating. The research data obtained by making observations, questionnaires/questionnaires, and documentation. The results showed that the pico hydro power plant worked well, indicated by the excellent product validation value. The waterwheel at the plant has a maximum power of 308 watts. In the development with the application of the MPPT type charger control regulator, results were obtained able to stabilize the electrical energy produced and increase the power capability of the power plant with the help of backup battery supply. For the results of the responses of the people of Kasambang Village, Mamuju Regency as many as 15 respondents, very decent results were obtained.